FRI0534 Repeated osteoporosis screening in rheumatoid arthritis: are we complying with guidelines?. (15th June 2017) - Gorman, A; Sullivan, V; Khan, S; Mohammed, A; O'Rourke, K
Abstract : Background: Osteoporosis rates are higher in patients with rheumatoid arthritis (RA). Patients with RA diagnosed with osteoporosis have a 30% increased risk of major fracture [1]. Monitoring response to osteoporosis treatment is recommended however there is no consensus on how frequently this should be performed. The International Society for Clinical Densitometry (ISCD), National Osteoporosis Foundation (NOF) and the American Association of Clinical Endocrinologists (AACE) all recommend repeat Bone Mineral Density (BMD) assessment within two years after initiating osteoporosis treatment to assess response to treatment [2–4]. Furthermore, the NOF and AACE recommend repeat screening every two years after diagnosis [3, 4]. Objectives: To identify patients with RA and osteoporosis To identify if international guidelines are being achieved for reassessment of BMD within two years of treatment commencement in keeping with international guidelines. Methods: A database of patients with a diagnosis of RA and osteoporosis who attend the Rheumatology department of the Midlands Regional Hospital, Tullamore since January 2013 was reviewed. Outpatient summaries, date of diagnosis, radiology investigations (DEXA scanning), pharmacological treatment and follow up investigations and treatment were documented. Results: As of August 2016, 770 patients were identified as having RA. 90% of patients had attended the department since 2013. 117 (16.7%) patients were identified as having osteoporosis. Of these, 52.14% of patients were prescribed bisphosphonate therapy, 31.62% denosumab, 9.4% calcium/vitamin D alone, 0.85% other treatment (teriparatide/strontium) and 5.1% were on no treatment. Only 11.9% of these patients had a repeat DEXA scan within two years of starting or changing treatment. 11.1% of patients had repeat DEXA scans booked. The average length of time since a patient's most recent DEXA is 35 months. Conclusions: Repeat DEXA scanning to assess the response to osteoporosis treatment in people with RA within the timeframe recommended by international guidelines has not been achieved. Patients who fail to respond to osteoporotic treatment are not being identified in a timely manner and therefore are at an increased risk of fractures. The results of this audit will make us more vigilant to identify those patients who are treated for osteoporosis that need repeat DEXA scanning to ensure that treatment is efficacious. References: Kanis JA, Johnell O, Oden A, et al. FRAX and the assessment of fracture probability in men and women from the UK. Osteoporos Int 2008; 19:385. 2013 ISCD Official Postions - Adult http://www.iscd.org/official-positions/2013-iscd-official-positions-adult/ (Accessed on December 02, 2013). Cosman F1, de Beur SJ, LeBoff MS, et al. Clinician's Guide to Prevention and Treatment of Osteoporosis Osteoporos Int. 2014 Oct;25(10):2359–81. Watts NB, Bilezikian JP, Camacho PM, Greenspan SL, et al.American Association of Clinical Endocrinologists Medical Guidelines for Clinical Practice for the diagnosis and treatment of postmenopausal osteoporosis. AACE Osteoporosis Task ForceEndocr Pract. 2010 Nov;16 Suppl 3:1–37. Disclosure of Interest: None declared